2015
DOI: 10.7575/aiac.ijalel.v.4n.6p.119
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Test Taking Strategy Instruction on Iranian High School Students’ Performance on English Section of the University Entrance Examination and Their Attitude towards Using These Strategies

Abstract: This paper reports on a study that investigated the effect of teaching test-taking strategies on Iranian high school students' performance on English section of the National University Entrance Examination (Konkoor). To do so, 273 male and female high school students participated in a workshop that lasted for four sessions. The participants were randomly divided into an experimental and a control group. In the beginning of the workshop, participants received a demographic questionnaire to see if they had taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The recommendations at present would probably be for teachers to improve their test-writing abilities. Takallou et al (2015) demonstrated that strategy training had a considerable positive effect on students' performance on the English section of University Entrance Examination test. Similarly, after the interventions carried out in the experiments described by Lee (2019aLee ( , 2019b, the experimental groups, which had received strategy training, significantly outperformed the control groups in the posttests.…”
Section: International Journal Ofmentioning
confidence: 97%
See 4 more Smart Citations
“…The recommendations at present would probably be for teachers to improve their test-writing abilities. Takallou et al (2015) demonstrated that strategy training had a considerable positive effect on students' performance on the English section of University Entrance Examination test. Similarly, after the interventions carried out in the experiments described by Lee (2019aLee ( , 2019b, the experimental groups, which had received strategy training, significantly outperformed the control groups in the posttests.…”
Section: International Journal Ofmentioning
confidence: 97%
“…When compared with the previous conceptualization of test-taking strategies by Cohen and Upton (2007), Tavakoli and Hayati Samian (2014) include test-management strategies under the heading of testwiseness strategies. Takallou, Vahdany, Araghi, and Nemat Tabrizi (2015) work with Bachman's (2000, p. 10) idea that one of the factors responsible for test performance is also "the processes and strategies used by test-takers in responding to test-tasks", saying these processes and strategies include test-taking strategies (p. 119). When compared with Cohen and Upton's division, they include test-wiseness, test management as well as some reading strategies in their research under test-taking strategies.…”
Section: Findings Delimiting the Scope Of Strategies Investigatedmentioning
confidence: 99%
See 3 more Smart Citations